REDESIGN KANTOR DAN MARKAS DINAS PEMADAM KEBAKARAN KABUPATEN BOGOR DENGAN PENDEKATAN AKTIVITAS DAN PERILAKU - Aurya Syazira, Dedrina; Salayanti, Santi; Nur Sheha Gunawan, Ahmad (Telkom University, 2024)
The Bogor Regency Fire Department is a government agency that is responsiblefor carrying out fire rescue tasks and non-fire emergencies in the Bogor Regency sector. Apart from handling problems regarding fire and non-fire emergencies, it is a center foreducation, DAMKAR administration and fire investigations. The building of the BogorRegency Fire Department has 2 general functions, namely as a headquarters and anadministrative office within the building. Apart from these two general functions, the District Fire Department. Bogor also provides space for education regarding fireprevention and management. After the analysis that has been carried out there are several groups of related problems such as space circulation as well as space needs and facilitiesfound in the field. This problem is related to the activities and behavior of building users at the Bogor Regency Fire Department. Therefore, in order for the District Fire Departmentto meet good operating standards, it is necessary to redesign the interior so that activities can run better and make the activities carried out within the District Fire Department more efficient. Bogor. Keywords: firefighters, activities and behavior, redesign